THE RELIABILITY OF A QUALITATIVE SCORING SYSTEM OF TRUNK AND LIMB ALIGNMENT DURING A 45-DEGREE SIDE STEP CUT. Issue 4 (28th April 2020) - Butler, Lauren; Milian, Erin; Latz, Kevin; Ellis, Henry; Martinez, Alexa; Hayden, Kristin; Gerstenkorn, Christian; Carpenito, Sara; DeVerna, Amie; Wyatt, Charles; Sugimoto, Dai; ,
Background: Three dimensional (3D) motion analysis is considered the "gold standard" for evaluating human movements. However, its clinical utility is limited due to cost, operating expertise and lengthy post-processing time. Numerous qualitative scoring systems, using videos, have been introduced to assess trunk and lower extremity (LE) alignment in dynamic maneuvers. However, it is unknown if a qualitative scoring system is a reliable method to evaluate cutting movement. Hypothesis/Purpose: To assess the inter-rater and intra-rater reliability of a qualitative scoring system to evaluate trunk and LE alignment during a 45-degree side step cut. The sub-aim was to investigate the effect of interactive peer discussion on inter-rater reliability. Methods: A repeated measures study design was used. Six raters (2 MDs, 2 PTs, and 2 ATs) independently viewed 10 videos, consisting of a 45-degree side step cut performed by adolescent male and female athletes. A clinically established checklist (Figure 1) was given to examine quality of movements. After the 1 st round, an interactive peer discussion was held to discuss videos, movement quality, and the checklist. Subsequently, after a 1-week wash out period, a 2 nd round of evaluation (examining the same 10 videos) was performed. Following the 2 nd round, and a 2-week wash out period, a 3 rd round was performed to assess intra-rater reliability. In each round, video sequences were altered in random order to avoid memory bias. Intraclass correlation coefficient (ICC) and their 95% confident intervals (95% CIs) were calculated. Values less than 0.50, between 0.50 and 0.75, between 0.75 and 0.90, and greater than 0.90 were defined as poor, moderate, good and excellent reliability, respectively. Results: Inter-rater reliability for the 1 st round was moderate (ICC: 0.565, 95%CIs: 0.074-0.866). Inter-rater reliability for the 2 nd round was better, however, was still moderate (ICC: 0.632, 95%CIs: 0.100-0.895). Intra-rater reliability between the 2 nd and 3 rd round ranged from moderate to excellent (ICC: 0.589-0.910). Conclusion: The results of this study showed moderate inter-rater reliability and moderate to excellent intra-rater reliability of the qualitative checklist. Following the interactive peer discussion, slight improvements in inter-rater reliability were observed. The findings indicate that this checklist may allow clinicians to standardize their assessment of trunk and LE alignment during a cutting task, however, more objective methods to evaluate multiplane movements, such as genu valgum, may be warranted. : Figure 1. 45-Degree Side Step Cut Checklist